Interpersonal Therapy Triumphs Over Postpartum Depression in Low Socioeconomic Contexts: Terapi Interpersonal Berhasil Atasi Depresi Pasca Melahirkan dalam Konteks Sosial Ekonomi Rendah - Hasanah, Desi Latifatul; Azizah, Nurul (Indonesian Journal on Health Science and Medicine, 2024)
This case study examines how low socioeconomic status influences postpartum depression (PPD) and evaluates the effectiveness of interpersonal therapy in managing PPD. A postpartum mother (Ny. R, 28 years old) was assessed using the DSM-IV, revealing major depression symptoms such as lack of interest, insomnia, fatigue, and feelings of worthlessness. Interventions included educating the mother on the physiological aspects of pregnancy and the benefits of exclusive breastfeeding, as well as implementing interpersonal therapy. These measures led to positive outcomes, with the mother beginning to care for her baby and seeking parenting information. The study underscores the importance of addressing socioeconomic factors in PPD and demonstrates the effectiveness of interpersonal therapy in improving maternal mental health. Highlights: Socioeconomic Impact: Low socioeconomic status increases postpartum depression risk. Therapeutic Success: Interpersonal therapy effectively manages postpartum depression. Holistic Approach: Combining psychological and socioeconomic support improves maternal mental health. Keywords: postpartum depression, socioeconomic status, interpersonal therapy, maternal mental health, case study